2011
DOI: 10.1227/neu.0b013e318209ce03
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Stenting of Extracranial Carotid and Vertebral Artery Dissections: A Systematic Review of the Literature

Abstract: Endovascular management of extracranial arterial dissection continues to evolve. Current experience shows that this treatment option is safe and technically feasible. Prospective randomized trials compared with medical management are needed to further elucidate the role of stenting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 81 publications
3
106
0
3
Order By: Relevance
“…Successful treatment has been reported as a result of the placement of a stent or other flow-diverting devices [18][19][20][21][22][23]. Although preservation of the parent artery is ideal, the durability of the perforating artery or the anterior spinal artery is not clear.…”
Section: Complications and Follow-upmentioning
confidence: 99%
“…Successful treatment has been reported as a result of the placement of a stent or other flow-diverting devices [18][19][20][21][22][23]. Although preservation of the parent artery is ideal, the durability of the perforating artery or the anterior spinal artery is not clear.…”
Section: Complications and Follow-upmentioning
confidence: 99%
“…Actually, improvements in stent technology may expand the population that may be eligible for endovascular treatment [30]. The use of new hemostatic agent as FloSeal (Baxter Biosciences, Vienna, Austria) could provides a quick and effective method of hemostasis in the bleeding by VA injury [1].…”
Section: Managementmentioning
confidence: 99%
“…As a result, he observed no severe complications during the operation and neither stroke nor de novo in-stent thrombosis/stenosis during a mean postoperative follow-up period of 28.7 ± 31.9 months. 11) Pham et al 12) performed meta-analysis in 140 patients in 31 studies on stenting for carotid artery dissection, and reported a technical success rate of stenting of 99%, procedural complication rate of 1.3%, mean postoperative follow-up period of 12.8 months, and in-stent stenosis or occlusion rate of 2%.…”
Section: Postoperative Coursementioning
confidence: 99%